(untitled) - Taziwa, Gerald

Calibrating rotation age for eucalyptus pellita and eucalyptus grandis x urophylla to optimize market returns for transmission poles and plywood in Ghana (Stellenbosch : Stellenbosch University, 2023)

(untitled)
Thesis (MScFor)--Stellenbosch University, 2023.